AKTIVITAS ANTIBAKTERI EKSTRAK KULIT MANGGIS (Garcinia mangostana L.) TERHADAP BAKTERI Haemophilus influenzae - Firdha Rachmawati; Novie Elvinawaty Mauliku; Arina Novilla; Rosa Nur'ainun Fauziyyah (LPPM Universitas Abdurrab, 2024)
Respiratory tract infections caused by the bacterium Haemophilus influenzae is a significant health concern due to the bacteria's resistance. Mangosteen peel extract (Garcinia mangostana L.) has potential as an antibacterial agent but is rarely applied to H. influenzae. This study aims to evaluate the antibacterial ability of mangosteen peel extract against the growth of H. influenzae. The mangosteen peel was extracted using the maceration method with ethyl acetate, and n-hexane as solvents. Through the diffusion method, ethyl acetate and n-hexane extracts at concentrations of 15; 30; 62,5; and 125 mg/mL were able to inhibit the growth of H. influenzae. The largest inhibition zone was observed at a concentration of 125 mg/mL, with an average diameter of 7,25 Â± 0,07 mm for the n-hexane extract and 8,7 Â± 0,71 mm for the ethyl acetate extract. It can be concluded that n-hexane and ethyl acetate extracts have antibacterial activity against the respiratory infection-causing bacterium H. influenzae, with the highest concentration being 125 mg/mL.